Instytucja udzielania ulg w spłacie zobowiązań z tytułu należności wynikających ze zwrotu środków europejskich - Solner, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The purpose of this article is to indicate principles of granting tax relief in the repayment of obligations resulting from the European funds refund based on the administrative resolution given by the administrative body in cases when European funds disbursed as part of operational programmes were used contrary to its intended purpose, with violating procedures, charged undue or in the excess height. The article distinguishes three types of tax relief: redemption in one piece or in part, postponing the repayment and spreading in instalments. It determines detailed principles of granting tax break for beneficiaries of not drivers of the business activity as well as for entrepreneurs, granted at the request of the beneficiary, as well as ex officio. The article is defining premises of granting these concessions i.e. the important interest of the taxpayer or the public interest. It is clarifying the principles of basing the administrative resolution on the administrative recognition and in case of entrepreneurs with reference to tax relieves constituting the state aid. The institution of granting concessions in the repayment is the exception from the principle of the universality and the equality of regulating these obligations. Irrespective of the entity initiating proceedings, relief can be granted only where justified, within the limits closely defined by the law. Granting it constitutes privilege of the beneficiary more than a rule
Keywords: dotacje unijne; finanse publiczne; fundusze strukturalne; Unia Europejska; prawo finansowe; terminy ustawowe; ulgi podatkowe